2020
DOI: 10.3390/jcm9082323
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Levels as a Mediator of the Detrimental Effect of Abdominal Obesity on Relative Handgrip Strength in Older Adults

Abstract: Excess central adiposity accelerates the decline of muscle strength in older people. Additionally, hyperglycemia, independent of associated comorbidities, is related to the loss of muscle mass and strength, and contributes to functional impairment in older adults. We studied the mediation effect of glucose levels, in the relationship between abdominal obesity and relative handgrip strength (HGS). A total of 1571 participants (60.0% women, mean age 69.1 ± 7.0 years) from 86 municipalities were selected followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…32 Other studies have also shown a negative correlation between excess abdominal adiposity, higher levels of glucose and triglycerides, and grip strength. 25,33 Furthermore, our study found that abdominal obesity explained (35.4%) changes in relative grip strength more than the other four metabolic components. In addition, our research result was consistent with other studies 31,34 showing that the MetS-relative grip strength association was mainly mediated by abdominal obesity.…”
Section: Relationship Between Metabolic Health Obesity and Relative Grip Strengthmentioning
confidence: 48%
See 1 more Smart Citation
“…32 Other studies have also shown a negative correlation between excess abdominal adiposity, higher levels of glucose and triglycerides, and grip strength. 25,33 Furthermore, our study found that abdominal obesity explained (35.4%) changes in relative grip strength more than the other four metabolic components. In addition, our research result was consistent with other studies 31,34 showing that the MetS-relative grip strength association was mainly mediated by abdominal obesity.…”
Section: Relationship Between Metabolic Health Obesity and Relative Grip Strengthmentioning
confidence: 48%
“…This result supports previous evidence in the elderly that has shown the negative effect of obesity on grip strength. 15 , 25 Some biological pathways (eg, inflammation, sex-specific hormones, anabolic resistance, and muscle denervation) likely contribute to obesity-induced muscle weakness. 26 , 27 Moreover, the identification of genetic variants for body fat metabolism may also provide an understanding of the development of physical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been reported that the direct effect of AO on R HGS was statistically significant. In addition, this study suggests that high glucose levels could worsen the association between AO status and lower HGS (31).…”
Section: Discussionmentioning
confidence: 72%
“…A recent study identifies a strong relationship between R HGS and the prevalence of MetS in adults, regardless of sex (36). On the other hand, in older adults, fasting glucose is inversely related to R HGS (31). Also, subjects with higher R HGS had a lower risk of HT, T2D and dyslipidemia than those with lower HGS (11).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, hyperglycemia and excess central adiposity are two independent factors that accelerate the decline in muscle mass and strength. Data showed that abdominal obesity was inversely associated with fasting glucose, and fasting glucose was inversely associated with HGS; thus, the fasting glucose level mediates the relationship between abdominal obesity and HGS [37]. Thus, causality between HGS and cardiometabolic markers, as well as their interaction with body composition, requires further prospective studies.…”
Section: Discussionmentioning
confidence: 99%